Mariborska deklaracija o pomenu knjižnic za kakovost univerz - Pivec, Franci (Organizacija znanja, 2007)
Accreditation, described as a "Licence to Kill", is arousing fear across Europe, since this American practice is unusual in the European context. The problem is the degree of autonomy of European universitie, which are under thecontrol of their governments, appropriating the authority for granting accreditations. In spite of different approaches to accreditation a common characteristic is ignoring the role of libraries in ensuring the quality of universities. Studies into the contribution of libraries are insufficient in Europe, requiring the reference to the results of the US CSEQ survey, undoubtedly proving that good universities cannot exist without good libraries. The librarians and information specialists from Southeast Europe discussed this issue at the COBISS 2006 conference and adopted the Maribor Declaration on the contribution of libraries to a higher quality of universities.
Keywords: akreditacija; bolonjska deklaracija; evalvacija; informacijska pismenost; knjižnice; student; študenti; univerze